Analysis Of Implementing Character Education In Students Sdn 060970 Belawan Medan - Muhammad Dekar; Dinda Widyastika; Rudi Hermansyah Sitorus; Zulvia Misykah; Mohammad Sattar; Muhammad Ridho; Azizul Kholis (Outline Publisher, 2024)
A developed and rapidly developing nation is one of the strategies implemented through character education with an honest, creative attitude and a sense of responsibility. The challenge in the current era of globalization is that character formation has not been realized due to a lack of control from parents and the environment, basically they are used to lying, low ethics and morals, loss of identity, rampant crime has penetrated every part of social life, hence the obligation of the education process. The real obstacle is that educational institutions use the metaphor of human resource (HR) products as having complete competence, known as the popular name digitalization competence in the 5.0 era. fundamental changes are inversely proportional to previous life governance. Educational science is a one-on-one medicine for diagnosing social ills in society from small to large circles. This research has a target regarding how teachers develop character education for students at State Elementary School 060970 Medan City. The method used in this research is qualitative description. The samples in the research were educators, homeroom teachers and students at State Elementary School 060970 Medan City. The instruments in this research are questionnaires to measure character education, stationery and video equipment. Research data was obtained through an interview and observation process. This research obtained results in the form of several students having positive and negative character education. Based on the results of interviews with educators and class teachers, character education planning is very effective, this is in line with national education goals, character education goals and the vision and mission of school 060970 SDN Medan CityKeywords: Analysis, Character Education, Students, Elementary School Teachers.